PENGEMBANGAN MEDIA BLOK PECAHAN PADA MATERI PECAHAN KELAS III SDN KRATON 2 BANGKALAN - Faizah Virgi Alifiana; Umi Hanik (Jurnal Sosial Humaniora dan Pendidikan, 2024)
This study aims to develop learning media for fraction blocks as learning media for grade 3 students at SDN Kraton 2 Bangkalan, which is expected to improve students' understanding of concepts in mathematics subjects of fraction material that has been explained by the teacher. This research is categorized as development research with reference to Sugiyono's model. The product developed by the researcher is a fraction block media that is well designed and attractive by combining images and texts that are adapted to the level of readiness and maturity of students in their age range. The first test subjects in this development research are expert subjects consisting of learning media experts, learning design experts, and learning material experts. Then, the second is the target test subject. This subject is divided into two, namely the product trial subject which uses 6 students from a total of 37 students of SDN Kraton 2 Bangkalan, and the usage trial subject which uses 31 students from the total students. The data collection techniques used by researchers are using observation instruments, interviews, questionnaires, and tests. Questionnaires in this study are divided into 2 types, namely expert validation questionnaires, which are used to determine the validity of fractional block media, and student response questionnaires, which are used to determine the attractiveness of the developed fractional block media. Then, the test is also used to determine the level of student understanding of fraction material after using fraction block media and also to determine the effectiveness of learning media to be developed. The results showed that, on the results of media validity carried out by learning media experts in the category of very valid, design experts and learning materials in the valid category. The results of the effectiveness level of the fraction block media with the category very effective and student learning tests get the effective category. The results of the attractiveness of fraction block media are included in the very interesting category which can be said to be interesting to use in learning.